Social media crimes against women: Examining legal remedies and enforcement mechanisms in India (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The rapid expansion of digital communication technologies and social media platforms has transformed the manner in which individuals interact, communicate, and participate in public discourse. While social media has created opportunities for empowerment, education, economic participation, and freedom of expression, it has simultaneously emerged as a platform for gender-based cyber violence and online exploitation against women. In India, the increasing penetration of smartphones, internet accessibility, and social networking applications has significantly increased incidents of cyber stalking, online harassment, cyber bullying, identity theft, revenge pornography, morphing of images, impersonation, sextortion, trolling, deepfake exploitation, and non-consensual circulation of intimate content targeting women. These forms of digital abuse not only violate the dignity, privacy, and autonomy of women but also create severe psychological, emotional, social, and economic consequences.The present article critically examines the growing nature of social media crimes against women in India and analyses the adequacy of the legal remedies and enforcement mechanisms available under Indian law. The study explores constitutional protections, provisions of the Information Technology Act, 2000, Bharatiya Nyaya Sanhita, 2023, Bharatiya Nagarik Suraksha Sanhita, 2023, Bharatiya Sakshya Adhiniyam, 2023, and other relevant legal frameworks aimed at protecting women from cyber victimization. The article also examines judicial trends, landmark case laws, cyber policing initiatives, role of cyber cells, digital forensic mechanisms, and institutional challenges faced in investigation and prosecution of cyber offences against women.The article further highlights socio-legal challenges including underreporting of cyber crimes, lack of awareness, victim blaming, jurisdictional complexities, anonymity of offenders, technological advancements, misuse of artificial intelligence, and inadequate digital literacy among users. The study emphasizes the necessity of strengthening cyber governance, digital awareness, gender-sensitive policing, victim support systems, and international cooperation to effectively combat social media crimes against women. The article concludes that although India has established a developing legal and institutional framework to address cybercrimes, stronger implementation, technological preparedness, legal reforms, and coordinated enforcement mechanisms are essential for ensuring meaningful protection of women in the digital age.